Pragmatic Functions of Directive Speech Acts in a TEDx Talk - Siti Fauziah Ikhsan; Khaulah Sholehah; Tatu Siti Rohbiah (General English Education, 2026)
This study aims to analyze the types, pragmatic functions, and persuasive contributions of directive speech acts found in the TEDx Talk video “How to Introduce Yourself and Get Hired” by Rebecca Okamoto, released on September 17, 2025. This study adopts a descriptive qualitative method with a pragmatic approach. The research data was taken from the video transcript and consists of 20 statements containing directive speech acts. Data analysis is based on the types of directive speech acts, delivery strategies, and pragmatic roles employed by the speaker. The research indicates that there are five types of directive speech acts: commands, suggestions, advice, requests, and invitations. Among these five types, suggestions and invitations are the most dominant, each accounting for 30%. The study also identifies that directive speech acts serve several pragmatic functions: instructing, guiding, engaging, and persuading. The use of direct and indirect strategies also helps speakers build interactions, create emotional connections, and strengthen persuasive communication with the audience. The results indicate that directive speech acts in TEDx Talks are not only used to provide instructions but also function as persuasive strategies to influence attitudes and increase audience engagement. Thus, this study contributes to research in pragmatics, particularly.